ADVANCING CLIMATE RESILIENCE THROUGH SUSTAINABLE FOREST MANAGEMENT: INTEGRATING ECOSYSTEM RESPONSE MODELING, ADAPTATION–MITIGATION STRATEGIES, AND CARBON CONSERVATION FRAMEWORKS - Gazala Yousuf Mir (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Forest ecosystems are increasingly recognized as essential components in strengthening climate resilience and addressing the growing challenges posed by global climate change. Effective forest management not only supports ecological stability but also contributes significantly to climate change mitigation and adaptation efforts. With the rising intensity and frequency of extreme climatic events, traditional forest management approaches require transformation toward more adaptive, science-based, and forward-looking strategies. This study emphasizes the integration of adaptation and mitigation measures within the framework of Sustainable Forest Management (SFM) to enhance ecosystem stability and long-term resilience. Anticipating how forest species and ecological processes respond to variations in temperature, precipitation patterns, and climatic extremes is fundamental for informed decision-making. The use of advanced monitoring technologies, predictive modeling, and early-warning systems enables managers to detect ecological shifts, including species redistribution, altered growth dynamics, and increased vulnerability to disturbances. Adaptation strategies involve modifying silvicultural practices, adjusting harvesting regimes, promoting climate-tolerant species, and improving overall forest productivity and regeneration capacity. Simultaneously, mitigation measures focus on strengthening carbon sequestration through afforestation, reforestation, improved forest conservation, and sustainable utilization of forest resources. The combined implementation of adaptation and mitigation strategies enhances forests’ capacity to function as resilient ecosystems while contributing to the reduction of greenhouse gas emissions. Given the critical role forests play in regulating the global carbon cycle, integrating carbon management into routine forestry practices is essential for achieving international climate objectives. A comprehensive and balanced management approach that incorporates ecological sustainability, economic viability, and social well-being is therefore necessary to ensure that forests continue to deliver ecosystem services and maintain their resilience under future climate uncertainties.